2017
DOI: 10.1111/1365-2435.12859
|View full text |Cite
|
Sign up to set email alerts
|

Linking animal contests and community structure using rockpool fishes as a model system

Abstract: Summary Competition for limiting resources is a fundamental and well‐established driver of niche partitioning, which in turn promotes species coexistence and biodiversity. Although contests are a well‐known behavioural mechanism by which organisms compete over limiting resources, there has been surprisingly little application of contest theory to understanding interspecific interactions, niche partitioning, species coexistence and biodiversity. We investigated the link between contest dynamics and community … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 71 publications
1
14
0
Order By: Relevance
“…Water was maintained at a pH of 8.5–8.6, a temperature of 22°C and a salinity level of 38–40 PSU. In the centre of each aquarium, a small rock (approximately 50 cm 2 ) that had been collected from the rocky shore was placed on small tiles to elevate it above the gravel to form a shelter (Paijmans & Wong, ). Fish were fed with thawed frozen brine shrimp daily.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Water was maintained at a pH of 8.5–8.6, a temperature of 22°C and a salinity level of 38–40 PSU. In the centre of each aquarium, a small rock (approximately 50 cm 2 ) that had been collected from the rocky shore was placed on small tiles to elevate it above the gravel to form a shelter (Paijmans & Wong, ). Fish were fed with thawed frozen brine shrimp daily.…”
Section: Methodsmentioning
confidence: 99%
“…While many contest studies have utilised fish as a model species to study elements of contest behaviour, the majority have focused on freshwater species (Beaugrand & Beaugrand, ; Chellappa et al, ; Cutts, Brembs, Metcalfe, & Taylor, ) with few focusing on marine species (Grossman, ). Further, fewer studies have focused on intertidal fish species (Paijmans & Wong, ) which is surprising given the interest in understanding factors governing community structure of intertidal organisms (Barjau‐González, Romo‐Piñera, López‐Vivas, Pérez‐Castillo, & Milicua, ; Kanamori, Fukaya, & Noda, ; Sorte et al, ). In the present study, the marine intertidal fish, Bathygobius cocosensis (Gobiidae), was used as a model species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bathygobius cocosensis vary in their morphology depending on whether they inhabit the low-tide or high-tide zone, with those from high-tide rock-pools being smaller on average and with eyes further up their heads (potentially for better vision of avian predators) (Malard et al 2016). Bathygobius cocosensis is an aggressive and territorial species (Paijmans and Wong 2017), and competition for food and habitat is intense particularly in the low-tide zone where there is better access to food and refuges. to match the background colour.…”
Section: Study System: the Intertidal Zone And Bathygobius Cocosensismentioning
confidence: 99%
“…Rapid growth can reduce mortality rates, by reducing time spent in the pelagic larval phase, and large settlement sizes often increase post-metamorphic survival ) and potentially competitive ability. Bathygobius cocosensis are an aggressive species, and larger individuals have been observed to inhabit rock-pools in the low-tide region of the intertidal zone (Malard et al 2016;Paijmans and Wong 2017), which generally provide greater access to food and refuges. Thia et al (2018) found that individuals of B. cocosensis that settle at a small size remain small for at least four days post-settlement, and larger B. cocosensis adults have also been observed to have higher routine metabolic rates than smaller individuals and faster burst swimming speeds (da Silva et al 2019a).…”
Section: Introductionmentioning
confidence: 99%